Recent advances in the functional explorations of nuclear microRNAs - Hu, Xiaozhu; Yin, Guoquan; Zhang, Yuan; Zhu, Liangyu; Huang, Haoyu; Lv, Kun (Frontiers in Immunology, 2023)
Approximately 22 nucleotide-long non-coding small RNAs (ncRNAs) play crucial roles in physiological and pathological activities, including microRNAs (miRNAs). Long ncRNAs often stay in the cytoplasm, modulating post-transcriptional gene expression. Briefly, miRNA binds with the target mRNA and builds a miRNA-induced silencing complex to silence the transcripts or prevent their translation. Interestingly, data from recent animal and plant studies suggested that mature miRNAs are present in the nucleus, where they regulate transcriptionally whether genes are activated or silenced. This significantly broadens the functional range of miRNAs. Here, we reviewed and summarized studies on the functions of nuclear miRNAs to better understand the modulatory networks associated with nuclear miRNAs.